PENGUKURAN KINERJA RANTAI PASOK DENGAN KEY PERFORMANCE INDICATOR (KPI) PADA PERUSAHAAN MANUFAKTUR SEPATU MENGGUNAKAN KONSEP GREEN SUPPLY CHAIN MANAGEMENT - Putra, Fadilah Ikhsan; Saryatmo, Mohammad Agung; Andres (Jurnal Mitra Teknik Industri, 2025)
The objective of this research is to develop prioritized indicators for companies by designing performance measurement using the Green Supply Chain Management (GSCM) approach, Key Performance Indicators (KPI), Supply Chain Operations Reference (SCOR) model, Objective Matrix (OMAX), and Traffic Light System to analyze environmentally friendly logistics strategies and concepts in support of corporate sustainability and efficiency. This study was conducted on a footwear manufacturing company. The performance measurement design, based on the green supply chain management concept aligned with the company's vision and mission, resulted in the identification of 45 key performance indicators. The company then selected 20 indicators out of the 45 proposed for further modeling using the Green SCOR method, which includes five perspectives: plan, source, make, deliver, and return. Performance scores were then calculated using the Objective Matrix (OMAX) and the Traffic Light System. The results showed that 12 indicators were marked green, 6 were yellow, and 2 were red. Each perspective received a score as follows, return 9.090, delivery 8.402, source 7.589, make 7.333, and plan 6. The plan perspective received the lowest score, indicating that immediate improvements should be made in the plan perspective, particularly regarding unmet indicators, to achieve the company’s performance targets.